2019
DOI: 10.25035/ijare.11.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Responses to Shallow Water Exercise: A Sex Comparison

Abstract: Acknowledgments The authors would like to thank Bryan Contreras and Lance Miller for technical and computer programming support. We would also like to thank Wilton Kanavan and Michael Dohrman for assistance with data collection. We would also like to thank the aquatic director, Debbie Nethery for coordinating pool availability and lifeguard support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Ten studies required special underwater equipment to conduct the protocol. Most papers did not report any pretest screening with some studies using health questionnaires or medical screenings [ 10 , 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Only one study [ 37 ] reported a land treadmill stress test as a pretest screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies required special underwater equipment to conduct the protocol. Most papers did not report any pretest screening with some studies using health questionnaires or medical screenings [ 10 , 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Only one study [ 37 ] reported a land treadmill stress test as a pretest screening.…”
Section: Resultsmentioning
confidence: 99%
“…Water temperature ranged between 27.5 to 32 °C and water immersion levels between waist/umbilicus to shoulders. Only six studies reported warm up [ 29 , 30 , 37 , 46 , 48 , 51 ]. Starting intensity and increasing intensity were based upon metronome setting or rate of perceived exertion (RPE).…”
Section: Resultsmentioning
confidence: 99%
“…Research on Tabata training was documented internationally [31,34,35,36,37]. However, there was still limited studies investigating the effects of the aquatic-based Tabata training method to improve physical fitness in athletes in situational sports.…”
Section: Introductionmentioning
confidence: 99%